(untitled) (The South Asianist Journal, 2014)
The Victoria and Albert Museum and Victoria Gardens is a significant Colonial institution, which reflects the aspirations and failings of the Indian and British elites that controlled late nineteenth century Bombay. The Museum crystallises the responses of these individuals to changes in thinking in Britain and its Indian Empire. As time passed, and each decision was made, the Museum evolved, in reaction to changes in the current social, economic, and political events of Bombay, Britain, and the Empire. Furthermore, the effect of these decisions and the fluctuating changes in opinion were dramatically reflected in the development of the Museum due to the slow progress of the building over a decade from 1858 to 1872.